Upaya Preventif melalui Edukasi dan Simulasi Gerakan Tanggap Bencana pada Masyarakat di Wilayah Pesisir, Desa Bokori, Kecamatan Soropia - Dewi Sartiya Rini; Rahmah Prahesti; Khusnul Khatimah; Nesi Arsita; Dwi Putra (Poltekkes Kemenkes Kendari, 2022)
Bokori Village is one of the areas in the coastal area of Soropia District, Konawe Regency which is located between a hill and the ocean. This condition is one of the causes of the high potential for disasters in the area. This community service activity aims to increase the knowledge and ability of the community in carrying out disaster response movements in the coastal area of Bokori Village. The method used in this community service is education and simulation as well as community assistance in carrying out disaster response movements. The potential result of this community service activity is an increase in the knowledge and ability of residents to carry out disaster preparedness marked by residents being able to independently carry out disaster response movements accompanied by a community service team. This activity is expected to be the first step in collaboration between health centers, educational institutions, and village officials in preventing disasters in coastal areas which in everyday life are still thick with belief in culture.